Management of Excellent Madrasa Program in Increasing Institutional Competitiveness - Jauhari, Irfan; Akhyak, Akhyak; Aziz, Abd.; Nur Ajizah, Ratna Utami (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2025)
This study explores the management of superior Madrasa programs in improving the competitiveness of institutions at MTsN 1 and MTsN 2 Ponorogo. Both institutions have their own uniqueness that is not possessed by other institutions, including a history of consistent competitiveness since their establishment in 1979. The focus of this study is on the planning, organization, implementation, and supervision of superior Madrasa programs. The study used a multi-site study method with a phenomenological approach and field research type. Data were collected through in-depth interviews, non-participant observation, and documentation studies, with snowball sampling techniques for selecting informants. The results of the study indicate that the planning of superior Madrasa programs involves mapping the talents and interests of students, developing a comprehensive curriculum, innovative learning methods, and teacher coaching. Organization is carried out through the formation of a special team, determining the structure and tasks, and monitoring and evaluation. Implementation involves student selection, curriculum implementation, innovative learning methods, intensive guidance, and comprehensive assessment. Supervision includes the formation of a special supervision team and the implementation of periodic supervision, as well as providing recommendations to related parties. This study confirms Henry Fayol's theory of management functions, namely planning, organizing, commanding, coordinating, and controlling. This finding provides an important contribution to the development of educational management in superior Madrasas to improve the competitiveness of institutions.